Penerapan Metode Drill And Practice Dalam Mencapai Tujuan Pembelajaran Pendidikan Agama Islam - Latipah, Siti Latipah; Maulidina, Ana; Sukma Ria Qurrota Ayun, Zuzun; Komalasari, Ratna; Asiah, Siti (Al-Mau'izhoh: Jurnal Pendidikan Agama Islam, 2024)
This research is motivated by how a teacher chooses and uses methods in the teaching process that are appropriate to the Islamic Religious Education subject matter, as well as the goals that must be achieved. Teachers in the teaching and learning process must experience development to improve the quality of education because teachers are one component of the educational process. This research method uses library research, namely a method of collecting data by understanding and studying theories from various literature related to the research. The drill and practice method is a technique that can be interpreted as a teaching method where students carry out practice activities so that students have higher dexterity and skills than what they have learned. So drill and practice is a teaching method that emphasizes lots of practice. The more practice, the more skilled students will be, so they will be effective in achieving the learning objectives of Islamic Religious Education.